2021
DOI: 10.5539/jas.v13n10p61
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Efficiency of Phosphorus Fertilizers With Associate Technology in Soy Crop in Cerrado Soil

Abstract: For commercial soybean production, the presence of phosphorus in the soil is essential, not only to increase productivity but also because it affects basic functions in plant metabolism. Phosphate fertilizers have low efficiency in Cerrado soils. For this reason, the use of technologies associated with phosphate fertilizers is important to increase their efficiency in the soil. The experiment was conducted at Fazenda Rio Brilhante in Coromandel, MG. The experiment was laid out in a randomized block design in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, though the application of Phosphorus increases the yield of soybeans, on the other hand, the application of surplus quantity will lead to adverse effects on the yield of soybeans (Khan et al, 2020). This position was supported by Soares et al (2021) who suggested that applying Phosphorus (P) fertilizer resulted in a positive response in Soybean grain yield as it facilitated the biological nitrogen fixation process by nodules in legumes, which depend on an ample Phosphorus supply. However excessive application of Phosphorus can restrict plant nodulation.…”
Section: Rate Of Fertiliser Appliedmentioning
confidence: 93%
See 2 more Smart Citations
“…However, though the application of Phosphorus increases the yield of soybeans, on the other hand, the application of surplus quantity will lead to adverse effects on the yield of soybeans (Khan et al, 2020). This position was supported by Soares et al (2021) who suggested that applying Phosphorus (P) fertilizer resulted in a positive response in Soybean grain yield as it facilitated the biological nitrogen fixation process by nodules in legumes, which depend on an ample Phosphorus supply. However excessive application of Phosphorus can restrict plant nodulation.…”
Section: Rate Of Fertiliser Appliedmentioning
confidence: 93%
“…Phosphorus is immobile in soil; therefore, plant uptake of Phosphorus may additionally be low in the first year after application (Tehulie et al, 2021). Studies have shown that using phosphate sources with associated technologies increased the soybean crop's relative agronomic efficiency and productivity (Soares et al, 2021). The following should be considered to achieve phosphorus fertilizer efficiency;…”
Section: Achieving Phosphorus Efficiency In Soybeanmentioning
confidence: 99%
See 1 more Smart Citation